The Implementation of Video Blogging to Improve English Speaking Skill and English Learning Motivation of Eleventh Grade Students - Arumsari Arumsari; Saly Kurnia Octaviani; Suryanti Galuh Pravitasari (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
This research aims to (1) describe the influence of video blogging implementation to improve English speaking skill of eleventh grade students in SMK (Vocational High School) Analis Kesehatan Nasional Surakarta for Academic Year 2019/2020, (2) describe the influence of video blogging implementation to improve English learning motivation of eleventh grade students in SMK (Vocational High School)  Analis Kesehatan Nasional Surakarta for Academic Year 2019/2020, and (3) describe the relation of English learning motivation and English speaking skill using video blogging.    This research applies descriptive qualitative to present the data which are collected with documentation. The subject of this research is the eleventh grade students in SMK Analis Kesehatan Nasional Surakarta for Academic Year 2019/2020 selected with purposive sampling.  The data are video and questionnaire from the eleventh grade students in SMK Analis Kesehatan Nasional Surakarta for Academic Year 2019/2020. From the assessment aspects of English speaking, the highest number of students take the score 4 with 38% students in grammar, 32 % students in vocabularies, 30% students in fluency, and 29% students in comprehension. Meanwhile, in pronunciation aspect, 33% students as the highest percentage acquires score 3. From these percentages, it shows that the implementation of video blogging is successful to increase the English speaking skill for eleventh grade students of SMK Analis Kesehatan Nasional Surakarta. From the English learning motivation questionnaires, 35% students strongly agree and 40% students agree showing the positive influence of video blogging as the media to learn English speaking for eleventh grade students of SMK Analis Kesehatan Nasional Surakarta in academic year 2019/2020. From the relation of English learning motivation and speaking skill, the high motivation of students to learn English produces the high score of English speaking skill for eleventh grade students of SMK Analis Kesehatan Nasional Surakarta in academic year 2019/2020.